2007
DOI: 10.1071/rd06086
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometry and expression of Cdc47 and caspase-3 in hyperthyroid rat uteri and placentas during gestation and postpartum associated with fetal development

Abstract: In two different experiments, the effects of hyperthyroidism on the histomorphometry and expression of Cdc47 and caspase-3 were evaluated in the uteri and placentas during gestation and postpartum. Fetal development was also evaluated during gestation. In the first experiment, 36 adult female Wistar rats were divided into two groups of 18 animals each: (1) hyperthyroid; and (2) euthyroid (control). Female rats were mated and killed at 7, 14 and 19 days of gestation. Uteri and placentas were weighed and subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
1
12
1
4
Order By: Relevance
“…As ratas hipertireóideas deste estudo tiveram nú-mero significativamente mais elevado de filhotes (11), o que poderia implicar piora da osteopenia lactacional, que é influenciada pelo número de filhotes (3). No entanto, o hipertireoidismo não agravou a osteopenia lactacional em nenhum dos sítios ósseos estudados.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As ratas hipertireóideas deste estudo tiveram nú-mero significativamente mais elevado de filhotes (11), o que poderia implicar piora da osteopenia lactacional, que é influenciada pelo número de filhotes (3). No entanto, o hipertireoidismo não agravou a osteopenia lactacional em nenhum dos sítios ósseos estudados.…”
Section: Discussionunclassified
“…A cópula era confirmada pela presença de espermatozóides no esfregaço vaginal, e este dia era designado como dia zero. As fêmeas que não apresentaram espermatozóides na citologia vaginal eram colocadas novamente com machos na noite seguinte, até que se encontrassem espermatozóides na citologia vaginal (11).…”
Section: Methodsunclassified
“…Furthermore, there is a reduction in the expression of inducible nitric oxide synthase (iNOS) 9 and intrauterine trophoblastic migration, which are important for vasodilation and intrauterine vascular remodeling (Silva et al 2012, Silva et al 2014, Silva et al 2015. Silva et al (2015) observed that hyperthyroidism reduces VEGF and Flk-1 expression in trophoblast cells at the end of pregnancy, which suggests that such changes might be related to preterm delivery that is exhibited by these rats (Kramer et al 2005, Freitas et al 2007, Andraweera et al 2012. However, evaluations of decidualization and the expression of angiogenic factors in the decidua and metrial gland of animals with thyroid dysfunction remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, hyperthyroidism promotes an increase in the birth rate without affecting weight or fetal viability (Freitas et al 2007). Hypothyroid rats exhibit compromised vasculature of the placental labyrinth and reduced trophoblastic expression of VEGF and its receptor Flk-1 by the end of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…1). Em estudos realizados em ratas, também não foi observada redução de peso decorrente do hipertireoidismo (Serakides et al, 2001;Freitas et al, 2007), ao contrário do que já foi relatado em humanos (Santos et al, 2002) e em gatos (Cardoso et al, 2005). Acredita-se que a redução de peso seja consequência de hipertireoidismo crônico e grave (Boelaert e Franklyn, 2005).…”
unclassified